Celiac Sprue and Abdominal Lymphoma: Studies on the Cell-Mediated Immune Response of Peripheral Blood Lymphocytes. (1988) - Davis, P.; Freeman, H.J.; Thomson, A.B.R.
Abstract : The development of primary abdominal lymphoma is a recognized complication of gluten-sensitive enteropathy (GSE). ln five patients with GSE plus lymphoma, the distribution and function of peripheral blood lymphocytes were determined and compared with 13 patients with GSE without lymphoma and with 28 normal control subjects. The percentage of T cells was lower in patients with GSE and GSE with lymphoma than in controls, whereas patients with GSE plus lymphoma had a significantly increased number of peripheral blood B lymphocytes when compared with GSE patients or controls. There was no difference in K cell activity or lymphocyte responses to mitogens and antigens between controls, GSE or GSE plus lymphoma patients. Prospective studies are needed in patients with GSE co investigate whether this fall in peripheral blood T cells and rise in B lymphocytes is a marker of concurrent lymphoma.